Når smerte er for det fælles bedste - Mortensen, Maria; Madsen, Karen Hvidtfeldt (K&K - Kultur og Klasse, 2015)
In a case study of a pain performance by Canadian Matthew Menczyk this article examines self-afflicted pain as a phenomenon both capable of transgressing dichotomous interpretations and creating connections between bodies, as well as oppositional concepts such as privat/public, mental/physical and personal/collective. By reading a sample of contemporary cultural-analytical pain-research, we demonstrate how pain is conceptualized within a framework of binary thinking. We question these dualistic understandings of pain, hereby showing how the Cartesian division is haunting the ontology of pain. The case of Menczyk is analyzed with reference to Michel Foucault’s writings on punishment and power. We show how self-afflicted pain points to the potential of pain as a place of resistance and healing and conclude that pain is not only to be understood as a condition-of-the-body, but rather as a phenomenon-in-and-of-the-world.